Cx3cr1 controls kidney resident macrophage heterogeneity - Yashchenko, Alex; Bland, Sarah J.; Song, Cheng J.; Ahmed, Ummey Khalecha Bintha; Sharp, Rachel; Darby, Isabella G.; Cordova, Audrey M.; Smith, Morgan E.; Lever, Jeremie M.; Li, Zhang; Aloria, Ernald J.; Khan, Shuja; et al. (Frontiers in Immunology, 2023)
Kidney macrophages are comprised of both monocyte-derived and tissue resident populations; however, the heterogeneity of kidney macrophages and factors that regulate their heterogeneity are poorly understood. Herein, we performed single cell RNA sequencing (scRNAseq), fate mapping, and parabiosis to define the cellular heterogeneity of kidney macrophages in healthy mice. Our data indicate that healthy mouse kidneys contain four major subsets of monocytes and two major subsets of kidney resident macrophages (KRM) including a population with enriched Ccr2 expression, suggesting monocyte origin. Surprisingly, fate mapping data using the newly developed Ms4a3Cre Rosa Stop f/f TdT model indicate that less than 50% of Ccr2+ KRM are derived from Ly6chi monocytes. Instead, we find that Ccr2 expression in KRM reflects their spatial distribution as this cell population is almost exclusively found in the kidney cortex. We also identified Cx3cr1 as a gene that governs cortex specific accumulation of Ccr2+ KRM and show that loss of Ccr2+ KRM reduces the severity of cystic kidney disease in a mouse model where cysts are mainly localized to the kidney cortex. Collectively, our data indicate that Cx3cr1 regulates KRM heterogeneity and niche-specific disease progression.